Chemotherapy of hematological malignancies in patients with COVID-19 - T. S. Chudnova; E. A. Baryakh; M. S. Litvinenko; T. N. Tolstykh; O. L. Kochneva; E. Y. Grishina; E. N. Misyurina; K. V. Yatskov; E. I. Zhelnova; Y. Y. Polyakov; K. V. Kaluzhskaya (Онкогематология)
In the era of COVID-19, the chemotherapy of patients with hematological malignancies has become the cornerstone in hematology. Secondary immunodeficiency as a result of hemoblastosis, predisposes to a more severe course of coronavirus infection, and specific antitumor treatment only exacerbates patients immunodeficiency. Thus, there is a problem of conducting chemotherapy during the COVID-19 pandemic. At the moment, there are no unified recommendations for risk assessment and choice of treatment for patients with oncohematological diseases and concomitant coronavirus infection. In this article, we present a series of clinical cases of patients with hematological malignancies diagnosed with coronavirus infection at the onset of a hematological disease or after chemotherapy. Patients with long-term persistent coronavirus infection requiring specific anticancer treatment were allocated to a separate group. We hope that this article will help to set a vector for further research, as well as serve as a clear example of the clinical situations that a hematologist may face during the COVID-19 pandemic.